A Survey of Correctional Education in Luzira Prison Uganda: Challenges and Opportunities - Aheisibwe, Irene; Rukundo, Aloysius (The International Journal Of Humanities & Social Studies, 2018)
The study aimed at exploring the challenges and opportunities experienced by prisoners on correctional education in Luzira Prison. Specifically, it examined challenges experienced by prisoners and the opportunities provided by correctional education. Across sectional survey design and the study was basically qualitative. The population was adult male and female convicted prisoners enrolled on correctional education, prison warders and instructors who were chosen purposively. Focus group discussion, Observation and interviews were used to collect data Permission was sought from all relevant officers and ethical considerations met. The study found out a number of challenges with regard to proper utilization of education a rehabilitative strategy for prisoners. These range from Stress and depression, infrastructure and other scholastic materials, poorly equipped Library, limited programs/ academic programs offered, transferring a prisoner from one prison to another during the course of study, limited time for revision and congestion. However, the study found a rich opportunity in education as rehabilitative strategy since many prisoners have had a n opportunity for free education, some have acquired several academic qualifications, some have been able to defend themselves in courts of law successfully, while others have continued to support their families through commissions received while still in prison.
Keywords: Correctional education; Challenges; Opportunities